Social Democracy in Europe - Delwit, Pascal; Ágh, Attila; Bell, David S.; Callaghan, John; Colomé, Gabriel; Gueorguieva, Petia; Ladrech, Robert; Marlière, Philippe; Moschonas, Gerassimo; Seiler, Daniel-Louis; Villalba, Bruno; Wiatr, Jerzy J. (Science politique, 2005)
Socialist and Social Democratic parties leave few political observers and citizens indifferent. For several years, a certain number of actors on the political scene have presented it as a political family in crisis, lacking in imagination and dynamism, incapable of renewal and doomed to fade into insignificance. Others, on the contrary, describe it as a grouping with a promising, even brilliant future.This book does not set out to confirm either of those two visions. Its aim is to analyse in-depth the transformations which are affecting, at the current time, the different aspects of Social Democracy: new organisational models, changes in political and electoral performance, changing relations with the trade unions and civil society associations, reactions to the emergence of new political rivais and new values, new ideological trends and political programmes, etc. For the first time, the analysis does not concern exclusively Western Europe, but also deals with the Social Democratic parties of the consolidated democracies and the organisations that claim to be part of democratic socialism in Central and Eastern Europe, and highlights the specific characteristics and points in common. At the dawn of the 21st century, it is therefore the challenges and the different responses to those challenges that are analysed by several of the leading European specialists in Social Democratic parties in Europe.